A cohort study of maternal screening for congenital Toxoplasma gondii infection: 12 years' experience - Yamada, Hideto; Tanimura, Kenji; Deguchi, Masashi; Tairaku, Shinya; Morizane, Mayumi; Uchida, Akiko; Ebina, Yasuhiko; Nishikawa, Akira (Journal of infection and chemotherapy : official journal of the Japan Society of Chemotherapy, 2019)
Primary infection with Toxoplasma gondii (T. gondii) during pregnancy may cause congenital infection of the infant. This study evaluated whether screening using IgG avidity and multiplex-nested polymerase chain reaction (PCR) methods was effective for detecting a high-risk pregnancy for congenital T. gondii infection. In a prospective cohort study serum T. gondii IgG avidity was measured in 469 pregnant women who had a positive test for T. gondii antibody plus a positive or equivocal test for IgM. Multiplex-nested PCR for T. gondii DNA on amniotic fluid, maternal blood, and neonatal blood was performed with informed consent. Low (<30%), borderline (30–35%), and high (>35%) IgG avidity indices were found in 104 (22.2%), 30 (6.4%), and 305 (71.4%), respectively. A total of 12 cases had a positive PCR test for amniotic fluids of the prenatal amniocentesis or at birth, or neonatal blood. Seven of the 12 cases were diagnosed as having congenital T. gondii infection, and they had low IgG avidity indices. Congenital T. gondii infection screening using of IgG avidity and multiplex-nested PCR methods for pregnant women with a positive test for T. gondii antibody plus a positive or equivocal test for T. gondii IgM was useful for detecting a high-risk pregnancy and diagnosing congenital T. gondii infection.